Galileo-E5a Bandwidth Frequency Filter Design for Galileo-E5a Receiver - Teerachet Mekpradab; Narumol Onanong; Surachet Chinnapark; Julongkorn Pattameak; Prasert Kenpankho (Universitas Pendidikan Indonesia (UPI), 2022)
This study focused on the design of the band-reject filter on the frequency of the Galileo satellite by providing bandwidth at the cut-off frequency equal to the bandwidth of the Galileo-E5a. The selecting of response characteristic is Butterworth's maximally flat, amplitude-frequency response of the band-reject filter. This poster shows the combination of the LPF and HPF to perform a band-reject filter. Therefore, there are two combinations also in designing for the band-reject filter. This combination aims to influence the performance of the band-reject filter. Band rejects filter design using the frequency of the Galileo-E5a with bandwidth is 25 MHz.using a Butterworth filter which is presented in this poster. The circuit is composed 3rd.order.Moreover, the combination between LPF and HPF is designed to act as a band-reject filter. As a result, we can filter the frequency of Galileo-E5a by using the band-reject filter.